2010
DOI: 10.1089/ten.tea.2009.0817
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Biochemical and Biomechanical Properties of Scaffolds Generated by Flock Technology for Cartilage Tissue Engineering

Abstract: Natural cartilage shows column orientation of cells and anisotropic direction of collagen fibers. However, matrices presently used in matrix-assisted autologous chondrocyte implantation do not show any fiber orientation. Our aim was to develop anisotropic scaffolds with parallel fiber orientation that were capable to support a cellular cartilaginous phenotype in vitro. Scaffolds were created by flock technology and consisted of a membrane of mineralized collagen type I as substrate, gelatine as adhesive, and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 57 publications
1
32
0
Order By: Relevance
“…In vitro studies of type I collagen hydrogel scaffolds has shown that the cells embedded in the hydrogel easily adhere and proliferate well and the MSCs seeded on type I collagen matrix, retain their differentiation potential for a long time. In one of the studies, it was reported that proteoglycan and type II collagen content were similar to that obtained by the same number of cells seeded on clinically used type I/III collagen scaffolds and cultured under the same conditions for 42 days [61]. Yuan et al [62] demonstrated the immunomodulatory properties of type I collagen hydrogel.…”
Section: Biomaterials Used For Cartilage Menisci and Ligaments Repaimentioning
confidence: 70%
“…In vitro studies of type I collagen hydrogel scaffolds has shown that the cells embedded in the hydrogel easily adhere and proliferate well and the MSCs seeded on type I collagen matrix, retain their differentiation potential for a long time. In one of the studies, it was reported that proteoglycan and type II collagen content were similar to that obtained by the same number of cells seeded on clinically used type I/III collagen scaffolds and cultured under the same conditions for 42 days [61]. Yuan et al [62] demonstrated the immunomodulatory properties of type I collagen hydrogel.…”
Section: Biomaterials Used For Cartilage Menisci and Ligaments Repaimentioning
confidence: 70%
“…Scaffolds could possess superior biomechanical properties and protect cells from early critical compression. Furthermore, oriented scaffolds fabricated from various materials using diverse techniques have been shown to possess superior strength and compressive modulus compared with typical non-oriented scaffolds in the dry state in vitro 21.…”
Section: Discussionmentioning
confidence: 99%
“…4 (C) and 4(D) show the FTIR spectra of the scaffolds flocked for 10 s and 30 s, respectively, and after immersion in SBF for 7, 14 and 21 days. The HA formation is confirmed by the appearance of bands at $ 567, 600 and 1017-1090 cm À 1 corresponding to the bending and stretching vibration of phosphate groups (PO 4 3 À ). The band at 878 cm À 1 corresponds to the vibration mode of carbonate groups (CO 3 2 À ) and suggests the formation of carbonated HA.…”
Section: In Vitro Bioactivity Studymentioning
confidence: 93%
“…Driven by increasing demand, new strategies for osteochondral TE are fast developing which involve the fabrication of bilayered scaffolds [3]. In case of cartilage damage, anisotropic scaffolds with parallel fiber orientation which provide columnar pore channels represent a suitable approach [4]. These types of scaffolds can be developed by flock technology [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation